THE USE OF CONJUNCTION: ELABORATION IN DONALD TRUMP’S SPEECH - Febru Setimaji; Teguh Abdulah; Acep Haryudin (IKIP Siliwangi, 2019)
Abstract Speaking is kind of communication that human needs to give same understanding of mind and works. The term of ‘speech’ has meaning to give some explanation from speaker to audience with many intention from the speaker based on their speech. The speech of Donald Trump at his first state on the january 2018 giving some explanation about the condition in USA today. This research giving the information about the use of conjunction: elaboration in Donald trump speech. The research goal to give some explanation about the types of conjunction and the meaning inside of it. This research used qualitative with the method have been used by the writers is textual analysis method as supported by Frey, et al. The analysis of data show us the precentage of subtype of conjunction: elaboration that Donald trump’s use at his speech are Expository 60%, Exemplifying 8%, Corrective 8%, Particularizing 8%, Resumptive 8%, Verifactive 8%. Donald Trump used appositive so often rather than using clarification on his speech. It means he is less doing clarification to have understanding between him and the audience